Multidisciplinary approach to the diabetic child - Marietti, Giovanni; Di Bernardo, Livia; Pantanella, Paolo; Metastasio, Paola; La Valle, Claudio (Medicina e Morale, 1989)
Diabetes is a chronic disease that is progressively increasing, especially in pediatric age, so now more than ever it is the subject of attention by scholars and health care facilities, the former aiming to know more about its etiopathogenetic mechanisms in order to diagnose the disease early and possibly prevent it, and the latter to prepare care that is appropriate for patients with the disease.